Prevention of mother-to-child transmission of HIV services in China: A conversation between healthcare professionals and migrant women with HIV. (3rd July 2018) - Lin, Chunqing; Li, Li; Ji, Guoping
ABSTRACT: In China, the access to prevention of mother-to-child transmission (PMTCT) of HIV services is particularly low among migrant population, which remains a challenge in the fight against HIV/AIDS. The study is aimed to investigate the PMTCT continuum for migrant women with HIV (MWHIV) and to identify barriers and potential strategies to improve the service delivery. The study started with a first round of focus group discussions with 20 healthcare professionals to map out the local PMTCT service cascade, followed by in-depth interviews with 20 recently delivered MWHIV to explore their perceived barriers along each step of the cascade, and a final round of focus groups with healthcare professionals to identify potential strategies to improve the PMTCT continuum. Lack of knowledge of antenatal care, stigma and discrimination in healthcare settings, inadequate provider–patient communication were major barriers hindering the PMTCT service utilization. Potential strategies to enhance the PMTCT uptake included broader publicity to the general population and using mobile phone application for health education. The issues of HIV-designated hospital and integration of postpartum and neonatal care were also discussed. The study allowed the healthcare professionals to recognize the service gaps along the PMTCT continuum and identified potential solutions for service improvement.